OPHIOLITE PULSES, MANTLE PLUMES AND OROGENY - Dilek Y. (My University, 2004)
Ophiolites show a wide range of internal structure, pseudostratigraphy and chemical fingerprints suggesting various tectonic settings of their origin. In general, they are characterized as mafic-ultramafic assemblages and associated sedimentary and metamorphic rock units that formed during different stages of the Wilson cycle evolution of ancient oceans, and that were subsequently incorporated into continental margins through collisional and/or accretionary orogenic events. Distributions of ophiolites with certain age groups in different orogenic belts define distinct ophiolite pulses, times of enhanced ophiolite genesis and emplacement, in Earth history. These pulses coincide with the timing of major collisional events during the assembly of supercontinents (i.e. Rodinia, Gondwana and Pangaea), dismantling of these supercontinents, and increased mantle plume activities that formed widespread large igneous provinces (LIPs). Suprasubduction zone ophiolites in orogenic belts signify oceanic crust generation in subduction rollback cycles during the closing stages of basins prior to terminal continental collisions. Both collision-driven assembly of supercontinents and deep penetration of subducted slabs into the lower mantle may produce plumes that in turn facilitate continental rifting, sea-floor spreading and oceanic plateau generation, all of which seem to have contributed to ophiolite genesis. Accelerated LIP formation and seafloor spreading that are associated with superplume events are likely to have caused widespread collisions and tectonic accretion of ophiolites at global scales. Together, these spatial and temporal relations suggest close links between ophiolite pulses, mantle plumes and orogenic events in Earth history.